Chemical composition and toxicity of the essential oil of Aloysia Paláu species (Verbenaceae) from South Brazil (Research, Society and Development, 2022)
In Brazil there are nine native species of Aloysia which are poorly studied as the chemical compositions and biological activities. Hence, this study describes the chemical composition determinated by GC-MS of essential oil of the five native and one cultivated species of Aloysia occurring in Rio Grande do Sul and evaluates the cytotoxic effects of the essential oils from A. citrodora, A. lycioides and A. dusenii through the bioassay with Artemia salina. A group of species showed 1,8-cineol as a major compound: A. dusenii (16.2 %), A. citrodora (32.8 %), A. lycioides collected in Guaiba (49.5 %) and A. lycioides collected in São Marcos (17.6 %). While species A. polygalifolia and A. virgata had higher proportions of germacrene-D (11.2 % and 12 %, respectively) and A. chamaedryfolia presented spathulenol (15.6 %). The species A. lycioides collected in Rosário do Sul had β-Phellandrene (23.7 %) as the major compound. All the essential oils tested presented a high toxicity against Artemia salina with LC50 values ​​among 48.12 µg mL-1 and 55.96 µg mL-1.